A rare presentation of intramuscular ganglion cyst in gastrocnemius muscle: a case report - Bhushan, Ravi; Madan, Harnam S.; Goel, Siddharth; Nupoor (International Journal of Research in Orthopaedics, 2024)
Ganglion cyst is a common benign cystic lesion but its presence at intramuscular region is rare. There are very few such reported cases in literature which are confirmed by histopathology. Here we are reporting a rare case of ganglion cyst in medial head of gastrocnemius muscle in a 20 year old male who presented with complaints of swelling in proximal aspect of left leg associated with occasional pain. The diagnosis was made on the basis of MRI and was confirmed histopathologically.